Cytogenetic and clinical characteristics of a case involving complete duplication of Xpter–>Xq13. Issue 3 (March 1996) - Jalal, S M; Dahl, R; Erickson, L; Zimmerman, D; Lindor, N
Abstract : True isochromosomes for Xp probably do not exist in a liveborn. We describe a rare case of complete Xp duplication and retention of the inactivation centre at Xq13. Cytogenetically, it is described as a nonmosaic 46, X, psu idic(X)(q13). Complete duplication of Xpter–>Xq13 was confirmed by banded analysis and FISH probes for X centromere, Xp21, XIST locus, and whole chromosome paints for X and Y. The abnormal X was always late replicating. Clinically, the patient was short statured, had primary amenorrhoea, and incomplete development of secondary sexual characteristics, but otherwise was phenotypically normal. There are no non-mosaic reported cases with complete duplication of i(Xp) confirmed by FISH or molecular techniques. Those cases with partial duplication of Xp and presence of the inactivation centre share the traits of amenorrhoea and poor secondary sexual development. To develop a clinical profile of duplication of Xp (in presence of Xq13) there is a need to study more cases.